Bargaining Exercices: beyond Simulation, A Touch of Reality - Gilson, Clive (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
Bargaining Exercices : Beyond Simulation; A Touch of Reality